Relationship between Information and Communication Technology (ICT) Literacy and Competencies and Public Universities Professional Secretaries’ Job Performance - Edun, Hakeem Jimoh; Soyebi, Gabriel Adewale (International Business Education Journal, 2022)
Universities professional secretaries’ job performance is crucial in ensuring the executives can carry out their academic and administrative functions effectively. Therefore, this study aims to determine the relationship between ICT literacy and competencies and job performance of professional secretaries in public universities in Southwest, Nigeria. Data collected from 609 professional secretaries are analyzed using descriptive statistics and correlation analysis. The findings of the study revealed a significant positive relationship between ICT literacy with ICT competencies and job performance. In conclusion, this study verifies the link between ICT literacy and job performance of universities professional secretaries. Hence, this study recommends professional secretaries to raise their ICT literacy to a more noticeable competent level that would contribute significantly to their job performance in public universities.